Peningkatan Kesadaran Penggunaan Alat Pelindung Diri dengan Pendekatan Fishbone Diagram dan Kaizen dalam Industri Herbisida - Prianto, Damar Wahyu (Fakultas Teknik UMRI, 2025)
Weeds compete with crops for nutrients, reducing agricultural productivity. While herbicides are commonly used to control them, their production exposes workers to chemicals that may cause mild to severe skin irritation. To minimize this risk, increasing employee awareness of personal protective equipment (PPE), particularly latex gloves, is essential. A fishbone diagram was used to analyze the root causes of low PPE usage, and improvements were implemented using the Kaizen method. Facility access was identified as the primary contributing factor. Corrective actions included relocating glove supplies closer to workstations. Comparative analysis between 2023 (before intervention) and 2024 (after intervention) showed significant improvements: glove usage ratio increased from 0.81 to 1.05, the correlation coefficient rose from 0.38 to 0.75, and the p-value decreased from 0.219 to 0.013. These results indicate a statistically significant increase in PPE compliance. Facility-focused interventions using continuous improvement strategies can effectively enhance occupational safety awareness and behavior.